The Critic Criticized: A Reply to Bruce MacDonald - Barbour, Douglas (Studies in Canadian Literature, 1977)
A brief response to Bruce MacDonald's article (SCL 1.2) points out the necessity for a range of critical response and discovers similarities within differing views of Ernest Buckler's The Mountain and The Valley, contributing to a movement towards a consensus concerning the novel.